Gall bladder stones: surgical treatment - S., Mohan S. V.; M., Shashidhara T.; Mehta, Sahil; Rajput, Akarsh S. (International Journal of Research in Medical Sciences, 2017)
Background: There is higher incidence of gall stones in Karnataka and more commonly seen in women aged between 25 to 55 years. In this study men are also encountered with gall stone. As all the gall stones cannot be removed by laparoscopic procedure, the complicated and adherent gall bladder with stones and where laparoscopic procedure is not available are removed by conventional open method of cholecystectomy and in this study open cholecystectomy procedure is dealt in detail. Methods: Open cholecystectomy through Right Kocher’s incision. Results: In this study of 10 cases with complications of gall stones dealt surgically by doing open cholecystectomy gave satisfactory postoperative results without much postoperative complications. Conclusions: Among 10 cases of open cholecystectomy 6 cases were done through duct first method and 4 cases were done through fundus 1st method, which gave good results and less postoperative complications.